The association between quality of life and subjective wellbeing among older adults based on canonical correlation analysis - Liu, Huanting; Gan, Qihui; Tan, Jianfeng; Sun, Xiaoyuan; Liu, Yuxi; Wan, Chonghua (Frontiers in Public Health, 2023)
This study explored the association between subjective well-being and quality of life among the elderly. Descriptive statistics were used to analyze the scores of general demographic characteristics, subjective well-being and quality of life. Simple correlation analysis and canonical correlation analysis were employed to analyze the relationship between subjective well-being and quality of life among elderly. Data from 892 older adults were collected. Canonical correlation analysis revealed four pairs of canonical variables, with the first four pairs of canonical correlation coefficients all being statistically significant (0.695, 0.179, 0.147, 0.121) (P<0.05), and the first pair of canonical variables explaining 93.03% of the information content. From the canonical loading coefficients, Vitality and mental health contributed the most to the quality of life (U1) canonical variable. The canonical variable V1, which corresponded to subjective well-being, was reflected by a combination of positive affect, negative affect, positive experience and negative experience. X1 (physical functioning), X2 (role-physical), X3 (bodily pain), X4 (general health), X5 (vitality), X6 (social functioning), X7 (role-emotional) and X8 (mental health) were positively correlated with Y1 (positive affect) and Y3 (positive experience), negatively correlated with Y2 (negative affect) and Y4 (negative experience). Cross-loadings revealed that physical functioning, bodily pain, general health, vitality, social functioning and mental health were the main factors reflecting the subjective wellbeing of older adults. As quality of life among the elderly was highly correlated with subjective well-being, appropriate measures should be taken to account for individual characteristics of the elderly, and various factors should be integrated to improve their subjective well-being.